On the through-process texture evolution assessment in grain oriented Fe-3 wt% Si steel produced by a novel directional inoculation technique - Snehashish Tripathy (Nature Portfolio, 2021)
Abstract A novel directional inoculation technique has been designed to cast thin slab ingots containing Goss (or near Goss) oriented components in the as cast microstructure under the combined effect of oriented nucleation and oriented growth. The same has been targeted so as to retain Goss orientations and simultaneously develop γ fiber components (ranging from {111}< $$1\overline{1}0$$ 1 1 ¯ 0 > to {111}<112>) during hot rolling. The designed scheme of directional inoculation achieved oriented nucleation by the effect of exogenously added soft magnetic inoculants under magnetic field and oriented growth by the effect of fast cooling rates prevailing in the mould. The choice of 65Fe–35Co (wt%) system as soft magnetic inoculants was made taking into account the similarity in crystal structure and lattice parameter. The chemically synthesized inoculants under the effect of external magnetic field during solidification were able to exhibit directional inoculation. Variation in the cast microstructure and microtexture by varying the extent of inoculant addition was studied by EBSD technique. The ingots cast under different conditions were subjected to a designed hot rolling schedule and the through process microstructural and microtextural evolution was assessed. It was observed that fine equiaxed grains with initial cube orientations in the as cast structure could lead to the most desirable microstructural as well as microtextural gradient in the hot band.